Endothelial arginase 2 mediates retinal ischemia/reperfusion injury by inducing mitochondrial dysfunction - Esraa Shosha; Abdelrahman Y. Fouda; Tahira Lemtalsi; Stephen Haigh; David Fulton; Ahmed Ibrahim; Mohamed Al-Shabrawey; R. William Caldwell; Ruth B. Caldwell (Elsevier, 2021)
Objective: Retinal ischemic disease is a major cause of vision loss. Current treatment options are limited to late-stage diseases, and the molecular mechanisms of the initial insult are not fully understood. We have previously shown that the deletion of the mitochondrial arginase isoform, arginase 2 (A2), limits neurovascular injury in models of ischemic retinopathy. Here, we investigated the involvement of A2-mediated alterations in mitochondrial dynamics and function in the pathology. Methods: We used wild-type (WT), global A2 knockout (A2KO-) mice, cell-specific A2 knockout mice subjected to retinal ischemia/reperfusion (I/R), and bovine retinal endothelial cells (BRECs) subjected to an oxygen-glucose deprivation/reperfusion (OGD/R) insult. We used western blotting to measure levels of cell stress and death markers and the mitochondrial fragmentation protein, dynamin related protein 1 (Drp1). We also used live cell mitochondrial labeling and Seahorse XF analysis to evaluate mitochondrial fragmentation and function, respectively. Results: We found that the global deletion of A2 limited the I/R-induced disruption of retinal layers, fundus abnormalities, and albumin extravasation. The specific deletion of A2 in endothelial cells was protective against I/R-induced neurodegeneration. The OGD/R insult in BRECs increased A2 expression and induced cell stress and cell death, along with decreased mitochondrial respiration, increased Drp1 expression, and mitochondrial fragmentation. The overexpression of A2 in BREC also decreased mitochondrial respiration, promoted increases in the expression of Drp1, mitochondrial fragmentation, and cell stress and resulted in decreased cell survival. In contrast, the overexpression of the cytosolic isoform, arginase 1 (A1), did not affect these parameters. Conclusions: This study is the first to show that A2 in endothelial cells mediates retinal ischemic injury through a mechanism involving alterations in mitochondrial dynamics and function.